CAPS and Munc13: CATCHRs that SNARE Vesicles - James, Declan J.; Martin, Thomas F. (Frontiers in Endocrinology, 2013)
Abstract. CAPS (Calcium-dependent Activator Protein for Secretion, aka CADPS) and Munc13 (Mammalian Unc-13) proteins function to prime vesicles for Ca2+-triggered exocytosis in neurons and neuroendocrine cells. CAPS and Munc13 proteins contain conserved C-terminal domains that promote the assembly of SNARE complexes for vesicle priming. Similarities of the C-terminal domains of CAPS/Munc13 proteins with CATCHR (Complex Associated with Tethering Containing Helical Rods) domains in multi-subunit tethering complexes have been reported. Multi-subunit tethering complexes coordinate multiple interactions for SNARE complex assembly at constitutive membrane fusion steps. We review aspects of these diverse tethering and priming factors to identify common operating principles.